Pedagogy or Technology? Understanding What Makes K-12 Students Stay Motivated in Indonesian e-Learning Platforms - Ni Kadek Vingki Aryanti; Ogi Suphar Gandi; Luh Putu Winda Yogantari (Universitas Pendidikan Ganesha, 2025)
The use of e-learning platforms in Indonesia, such as Ruang Guru, Zenius Education and Quipper Video, has been scaling up. Since they are self-paced learning platforms, previous studies put into questions how students stay motivated to learn in such self-relied online learning. Therefore, this study aims at examining and explaining how the content, instructors, teaching strategy, visual design, usability and learnability of the platforms affect students’ motivation to learn. Sequential mixed method research design was applied to answer the aims. The first stage was the quantitative data collection using questionnaire. It gained 140 responses from senior high schools’ students who have used the platforms. After analysing the questionnaire using multiple regression, three respondents were purposively chosen to participate in a qualitative interview. Then, the interview was transcribed, categorized, and translated into English. The qualitative and quantitative result agree that teaching strategy and content learned in the platforms significantly affect students to stay motivated to learn. Additionally, but importantly, instructors, from the interview, have found to be another factor that influences students to stay motivated to learn. However, visual design is not found as a significant factor influencing students’ motivation to learn. Usability and learnability of the platforms, also, cannot be concluded whether to influence students or not, because students never experience technical issue. In general, this study suggests to instructional designer and educators to consider pedagogical aspects such as content, teaching strategy, instructor’ role and communication in their online learning design.